SANGGAHAN MUHAMMAD ABU ZAHW TERHADAP KELOMPOK INKAR SUNNAH DALAM KITAB AL-HADITS WA AL-MUHADDITSUN - Mohamad Soleh (CV. Adiba Aisha Amira, 2023)
The development of hadith was not free from various obstacles and problems. Some of the problems that arose included the existence of groups that were skeptical of the originality of the hadith. This is because hadiths were narrated and transmitted orally for more than a century and were only codified during the leadership of Caliph Umar bin Abdul Aziz. This paper will discuss Muhammad Abu Zahw's refutation of the inkar sunnah group. The results of this study indicate that; First, Muhammad Abu Zahw is an Egyptian hadith expert who divides the periodization of hadith into seven periods from the time of the Prophet to the present. Second, the inkar sunnah group is an understanding that denies or rejects the Prophet's ï·º traditions either entirely or only aá¸¥Äd traditions. Thirdly, the inkar sunnah group has misinterpreted the Qur'anic verses that are used as evidence in rejecting the Prophet's ï·º traditions. As for the aá¸¥Äd traditions, they cannot be rejected because the Companions and the Taabi'in have agreed to accept the aá¸¥Äd traditions.